PENGARUH BIAYA PRODUKSI, BIAYA OPERASIONAL, DAN PENJUALAN TERHADAP LABA BERSIH PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016 - Ros tiati; Herlina Ferliyanti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This aim of this research is to examines the effect of production cost, operational cost, and sales to net income. The population of this research are listed company of manufacturing in Indonesian Stock Exchange (IDX) period 2012-2016. Based on purposive sampling method, total sample in this research are 21 companies. The analysis used to research is tested with descriptive statistics test, panel data testing, normality data test, and hypotesist test. The tools used to analysis for this research by using Eviews 9. The result of this research indicate that based on test partial (T-test) production cost and sales had effect to net income with probability value 0.0086 and 0.0000 < 0.05. While, operational cost had no effect to net income with probability value 0.9380 > 0.05. Simultaneously (F-test), production cost, operational cost, and sales had effects to net income with a probability 0.0000 < 0.05.